Nonfat Set Yogurt: Effect of Okra Gum and Various Starches on the Rheological, Sensory, and Storage Qualities and Wheying-Off - Ali Saleh; A. A. Mohamed; M. S. Alamri; S. Hussain; A. A. Qasem; M. A. Ibraheem; Syed Ali Shahzad (Journal of Chemistry)
This work was intended to determine the effect of okra gum in combination with various starches on the flow and sensory properties of nonfat set yogurt. The selected starches include potato (PS), sweet potato (SPS), corn (CO), chickpea (CP), and Turkish beans (TB). The control is the yogurt prepared with okra gum only. Samples were analyzed under optimum conditions for their shear viscosity, viscoelasticity, texture, wheying-off, and sensory evaluation. Tests were performed at the beginning of the cold storage and after 7 or 15 days. By adding 1.0% starch, significant (p<0.05) reduction in wheying-off and firmer yogurt was obtained. Variations in the properties of yogurt were obvious and can be attributed to starch origin and amylose content. Therefore, the qualities of yogurts with tuber starches (PS and SPS) were different compared to corn or legume starches (CP and TB). The effect of the starches on yogurt properties changed over storage time, where some starches performed better only at the beginning of the storage period, and steady pH was maintained throughout the storage time. Wheying-off was significantly reduced irrespective of the origin of the starch. Sensory evaluation showed preference for yogurts prepared with starch compared to the control, regardless of starch type. Nonetheless, CP was preferred over other starches with respect to wheying-off, power law parameters, and overall acceptability.